Costs and Benefits of Euro Adoption in Bulgaria - Georgy Ganev (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This study presents a cost-benefit analysis of euro adoption for the case of Bulgaria. Based on a review of existing similar studies for other East European EU member states, it outlines the basic types of potential costs and benefits of euro adoption, and applies them to the specific Bulgarian economic and economic policy context. The most important relevant features of the Bulgarian economy with respect to the analysis are found to be the catching-up status of the country and the currency board arrangement. In this context the study finds that a net benefit of above 15 % of GDP in a 20 year horizon can be expected for Bulgaria due mainly to enhanced capital inflows and to a smaller extent to a boost in trade with the EU and to higher domestic saving in light of enhanced policy credibility. Along the way the study attempts to draw attention to important nuances which may be of relevance for the analysis of euro adoption in Eastern Europe in general.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: E52; F15; F33; F42; 330; Bulgaria; euro area; euro adoption; cost-benefit analysis